Beyond justice as fairness rethinking Rawls from a cross-cultural perspective - Nnodim, Paul (Lexington Books, 2020)
"This book explores the three foundational topics in Rawls's theories of justice (social justice, multiculturalism, and global justice) while deconstructing ideas of democratic citizenship, public reason, and liberal individualism latent in his treatment of these subjects in order to uncover their cultural and historical underpinnings"--